Multidrug resistance of Pseudomonas aeruginosa: do virulence properties impact on resistance patterns? - Saha, Poulomi; Kabir, Rubaiya Binte; Ahsan, Chowdhury Rafiqul; Yasmin, Mahmuda (Frontiers in Microbiology, 2025)
IntroductionPatients with nosocomial infections are at risk of multidrug-resistant (MDR) Pseudomonas aeruginosa since these bacteria slow down the entire treatment process, increasing the morbidity and mortality of patients staying in hospital. The purpose of the research was to assess the simultaneous presence of multidrug resistance and virulence factors among nosocomial strains of P. aeruginosa to evaluate significant association among them.MethodsOne hundred and eight clinical isolates of P. aeruginosa were found in a variety of samples taken from patients having nosocomial infection, including wound swabs, pus, sputum, tracheal aspirate, and urine. An antibiogram was performed to investigate the pathogen’s antibiotic sensitivity pattern against 14 widely used antibiotics in Bangladesh. Virulence factors were evaluated, and the presence of ten β-lactamase and six virulence genes was analyzed by performing PCR. By using a binary logistic regression test with a 95% confidence interval, the relationship between MDR phenotypes and the virulence attributes was assessed.ResultsThe susceptibility rate among the isolates was 70–75% for aminoglycosides (amikacin, gentamicin, netilmicin), 15–20% for cephalosporins (ceftazidime, ceftriaxone), 30–35% for quinolones (ciprofloxacin, levofloxacin), 10–15% for tetracyclines (tigecycline, doxycycline), 15–20% for carbapenem (meropenem), 10–15% for sulfonamide (co-trimoxazole), 5–10% for amoxiclav, and 30–35% for piperacillin/tazobactam. A total of 74.1% of the strains carried metallo-β-lactamase (MBL) genes. Among the isolates, 89% showed hemolytic activity, 80–90% produced different pigments such as fluorescein and pyoverdine, 46% were strong biofilm producers, and all the isolates presented different types of motilities (swimming, swarming, and twitching). The virulence genes (lasB, exoS, toxA, aprA, algD, and plcH) were detected within a range of 60–80% of the isolates.DiscussionOnly the toxA gene and twitching motility showed a significant correlation (p-value = 0.001 and 0.028, respectively) with multidrug resistance in the clinical P. aeruginosa isolates which indicates that it can be used as a drug target to combat these organisms. The high prevalence of MDR strains and their association with virulence factors revealed the potential of the pathogen to cause an infection. The current study advocates for immediate epidemiological surveillance of MDR P. aeruginosa strains in Bangladesh to impede the rapid dissemination of this opportunistic pathogen.